Corrosion Behavior of AZ91D Magnesium Alloy in Three Different Physiological Environments - Zhou, Juncen; Li, Qing; Zhang, Haixiao; Chen, Funan (Journal of Materials Engineering and Performance, 2014)
Magnesium alloys have been considered as promising biomedical materials and were studied in different physiological environments. In this work, corrosion behavior of AZ91D magnesium alloy in artificial saliva, simulated body fluid (SBF), and 3.5 wt.% NaCl solution was investigated using electrochemical techniques and a short-term immersion test. In contrast with other physiological environments, the amount of aggressive ions in artificial saliva is small. In addition, a protective film is formed on the surface of samples in artificial saliva. Experimental results suggest that corrosion resistance of AZ91D magnesium alloy in artificial saliva is better than that in c-SBF and 3.5 wt.% NaCl solution.